Cover Feature: 4‐Thiouridine‐Enhanced Peroxidase‐Generated Biotinylation of RNA (ChemBioChem 1/2021). (16th December 2020) - Huang, Jinguo; Zhao, Ruiqi; Qin, Shanshan; Yang, Shixi; Li, Wei; Mo, Jing; Wang, Fang; Du, Yuhao; Weng, Xiaocheng; Zhou, Xiang
Abstract : The s 4 U button has more power to catch RNA toys : There is growing interest in RNA techniques. Engineered ascorbate peroxidase (APEX2) was discovered to react with guanine, and generate RNA proximity labeling tools. But the RNA labeling efficiency still has room for improvement. We found that the metabolic incorporation of 4‐thiouridine can introduce additional reactive sites for RNA labeling, and improve the efficiency of the peroxidase‐generated biotinylation of RNA. More information can be found in the full paper by X. Weng et al.